2020
DOI: 10.1101/2020.02.07.939181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DKW basal salts improve micropropagation and callogenesis compared to MS basal salts in multiple commercial cultivars ofCannabis sativa

Abstract: Micropropagation of Cannabis sativa L. is an emerging area of research for genetic storage and large-scale production of clean planting material. However, existing protocols were developed using a limited number of genotypes and are often not reproducible. Previous studies reported MS + 0.5 μ M TDZ to be optimal for Cannabis micropropagation, yet in our preliminary studies this medium resulted in excessive callus formation, hyperhydricity, low multiplication, and high mortality rates. Following an initial scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 31 publications
7
50
1
Order By: Relevance
“…Work by Page et al . [9] has shown that the use of DKW media [28] may promote increased levels of callogenesis in some Cannabis genotypes, suggesting that media composition and genotype may interact to affect the formation of callus and subsequent regeneration potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Work by Page et al . [9] has shown that the use of DKW media [28] may promote increased levels of callogenesis in some Cannabis genotypes, suggesting that media composition and genotype may interact to affect the formation of callus and subsequent regeneration potential.…”
Section: Resultsmentioning
confidence: 99%
“…The most successful protocols report between 9 and 13 shoot explants per nodal segment [4,7]. Unfortunately, most existing protocols were developed using a single high-THC genotype of C. sativa , and recent evidence suggests that methods developed using a single genotype are not replicable when tested on commercially available drug-type C. sativa genotypes and that multiplication rates are much lower, around 2.2 shoots per explant [9]. In addition to low regeneration rates, MSC is unsuitable for some biotechnological applications, and cannot compete with the relative ease of traditional vegetative propagation methods for large-scale commercial plant propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media composition. A previously optimized semi-solid tissue culture medium (Page et al, 2020) that consisted of 5.32 g/L DKW basal salts and vitamins (D2470; PhytoTech Laboratories, Shawnee, KS) (Driver and Kuniyuki, 1984), 30 g/L sucrose, 1 mL/L plant preservative mixture (PPM) (Plant Cell Technology, Washington, DC), and 6 g/L of agar (A360-500; Fisher Chemical, Fair Lawn, NJ) adjusted to a pH of 5.7 before being autoclaved was used. Approximately 200 mL of the medium was poured into the bottom of each sterile We-V tissue culture vessel.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro flowering and seed set have been proposed in other species as a valuable tool to reduce generation time for applications in plant breeding and to study floral/seed development in a highly controlled environment (Ochatt et al, 2000). Additional aspects specific to cannabis may include the opportunity to study the regulation of secondary metabolites, production of floral tissue for plant regeneration (Piunno et al, 2019), and the potential to rapidly identify the critical photoperiod of specific genotypes.…”
mentioning
confidence: 99%